Indian Commodity Derivatives Market : Structural Breaks and Price Discovery - Singha, U. Sarita; Singh, N. B.; Mutum, Kelvin (Indian Journal of Finance, 2024)
Purpose : The purpose of this research was to determine structural breakpoints and examine the causal relationship between the spot and futures markets for 12 commodities that are traded in India. Methodology : Data were obtained from the Multi Commodity Exchange of India Limited (MCX) website for both futures and spot price series of 12 commodities, including agricultural commodities (crude palm oil (CPO), mentha oil, and cotton), energy commodities (natural gas and crude oil), precious metals (silver and gold), and base metals (lead, zinc, aluminum, copper, and nickel). Structural breaks were identified using a multiple breakpoint test, and the price series were segmented into sub-periods. Subsequently, the Granger causality test was conducted within a vector autoregressive (VAR) framework to examine causal relationships between the spot and futures markets. This analysis was conducted for the entire study period and for sub-periods identified by structural breaks. Findings : Bidirectional relationships were observed for the whole period across all commodities, indicating market efficiency. Nonetheless, in certain sub-periods, unidirectional causality was noted, indicating potential structural fractures brought on by events influencing market efficiency on the political or economic front. Practical Implications : The findings of this study are valuable for various stakeholders, including individual and institutional investors, policymakers shaping regulatory frameworks, market regulators, exchange facilitators, and other relevant authorities. These insights contributed to informed decision-making, robust policy formulation, improved regulatory oversight, and the enhancement of market integrity and stability. Originality : This study contributed to the literature by considering structural breakpoints in the analysis of price discovery and market efficiency in the Indian commodity derivatives market, an aspect that has been relatively underexplored in previous studies.